Analisis Maqashid Syariah terhadap Putusan Verstek dalam Cerai Gugat pada Putusan Nomor 440/Pdt.G/2022/PA.Kng) - Mukhlis Hidayat, Endang (El 'Ailaah, 2024)
The absence of the defendant or husband in the process of examining a divorce lawsuit case causes the judge deciding the case with a verstek decision. This research aims to produce findings in the form of considerations used by the Panel of Judges in case Number 440/Pdt.G/2022/PA and then analyze the considerations in reviewing maqashid sharia. The research method in this research is a qualitative research method with a combined type of research, namely field research and library research. Apart from that, the data collection techniques used were interviews and documentation using descriptive analysis techniques. The results of this research found that the judge's considerations in decision Number 440/Pdt.G/2022/PA.Kng included the defendant's absence from the trial, the fulfillment of the requirements to advise the plaintiff to maintain his household, the failure to carry out the mediation process, and proof of the suitability of the witness statement with the evidences presented by the plaintiff, as well as ongoing disputes between the plaintiff and the defendant so that their household cannot be reconciled. These considerations in the review of maqashid sharia are considered to have maintained benefits, eliminated harm and fulfilled maqashid sharia in 4 (four) aspects; hifdz ad-din, hifdz an-nafs, hifdz al-‘aql, hifdz al maal. Keywords: Verstek Decision, Divorce, Maqashid Sharia